Examination of the accuracy and usefulness of Garmin and Suunto GNSS devices during navigation of the TS-11 “Iskra” jet aircraft - Ciećko, Adam; Grunwald, Grzegorz; Kaźmierczak, Rafał; Dobek, Marek; Gołąbek, Piotr (International Conference “Environmental Engineering”, 2017)
This study was designed and performed in order to determine the accuracy and usefulness of different modern Garmin and Suunto GNSS devices – mainly smartwatches – during a flight of TS11 “Iskra” aircraft. The plane trajectory was determined using six different navigation devices placed in a cockpit of an aircraft. To calculate reference position – Thales Mobile Mapper with postprocessing option and data from Polish ASG-EUPOS network was used. The obtained results show that the tested devices gave reasonable positioning accuracy and can be used on board of an aircraft traveling at high speeds. However, it must be emphasized that smartwatches can be only used as a supplementary navigation aid during any air operation.